Factors Related to the Turnover of Health Personnel in the Deep Southern Provinces.A Case Study of Yala Province - Jirasrattasiri, Marut (Journal of Health Science of Thailand, 2018)
This qualitative research had an objective to investigate the factors related to the turnover of health personnel in the deep southern provinces of Thailand: a case study of Yala Province. As a result, positive policy was to be developed in order to retain of health personnel in this area. Samples of this study were selected from all health professions in provincial, district, and sub-district levels including: physicians, dentists, nurses, health workers, and heads of general administration of community hospital. The samples were divided into 2 groups including (1) health personnel who work in Yala province before the South insurgency and still remained there. There in addition, they had been working in Yala province for at least, 5 years, (2) health personnel who moved out from Yala province. For the first group, focus-group discussion was conducted in 26 health staffers and indepth interview of 6 health staffers. For the second group, in-depth interview was also conducted in all 7 health staffers who moved out or resigned their posts. This study was conducted from December 2550 to April 2551. (1) The factors cited by those remained working in Yala Province included: natives of Yala province with family support and encouragement. In addition, health personnel who work in the unrest provinces received financial incentive. For working environment, they had good colleagues, good supervisors, developing a bond with their careers, working enthusiasm, and working appreciation. They felt obliged to work for peoples who lived in remote areas and they hoped the situation would be improved sooner or later. The religious principles were spiritual adherence for virtue. (2) The important factor that drove health personnel to move out or resign posts included life threatening violence, impacts on their families, life threats, and non-smooth working environments. Moreover, they had difficulty adjusting daily activities. These made them less self-assertive, fear ful, and stressful. (3) The factors that enhanced health personnel to remain in their posts with high competency included welfare, salary, extra pay for risky area, supporting of working materials, reduced gap between professions, and supporting of life insurance, field supervision and attention of executives, fair and efficient human resource management. It is recommended that high ranking executives with vision and comprehensive perspective should be appointed and in-charge in this area. A security system and family support should be set up to avoid the threat and heal the wound. In addition, natives recruitment should be encouraged.